2011
DOI: 10.1080/13218719.2011.559155
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recidivistic Arson in Adult Offenders

Abstract: This article reviews the current literature on known risk factors for recidivistic arson, with a particular focus on factors that could be used to differentiate serial from 'one-off' arson offenders. The relevance of risk factors for general reoffending to recidivistic arson is discussed, including the role of criminal history, mental illness, and sociodemographic factors. The specific roles of offence related affect, cognitions, and the offender's interest in fire are considered, with recommendations for how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Previous work has examined risk factors for arson, finding that substance misuse and criminal history are predictive of adult offending (Doley et al, ). In addition, prior antisocial behaviour, including deviance, vandalism and aggression, has been correlated with juvenile firesetting (Fineman, ; Slavkin and Fineman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has examined risk factors for arson, finding that substance misuse and criminal history are predictive of adult offending (Doley et al, ). In addition, prior antisocial behaviour, including deviance, vandalism and aggression, has been correlated with juvenile firesetting (Fineman, ; Slavkin and Fineman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Even if such a formula could be derived, the existing literature lacks the consistency required to identify valid risk factors related to recidivistic arson with any confidence (Davis & Lauber, ). Inconsistent definitions of recidivism and variability in sample composition of firesetters pose particular problems for this literature (Doley, Fineman, Fritzon, Dolan, & McEwan, ). In an attempt to help move the field forward, we conducted a study of more than 1,000 people convicted of arson and arson‐related offences over a 10‐year period.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of few representative studies on the risk factors for repeat firesetting, there are some consistent findings reported (Doley et al ., ). Common factors include: being single (Dickens et al ., ; Rice & Harris, ); having family dysfunction, poor school adjustment, unemployment, personality and psychiatric disturbance but not psychosis (Dickens et al ., ; Doley, ; Rice & Harris, ); younger age at index and at first firesetting, past history of firesetting, early fascination with fire and firesetting alone (Del Bove & Mackay, ; Dickens et al ., ; Rice & Harris, ; Soothill & Pope, ); and history of property crime and general criminal history (Barnett & Spitzer, ; Doley, ; Repo, Virkkunen, Rawlings, & Linnoila, ; Rice & Harris, ; Soothill et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, clinicians appear to have presumed that firesetters as a population are generalist offenders due to their diverse criminal histories and shared characteristics with other offenders (Doley, Fineman, Fritzon, Dolan, & McEwan, 2011;Gannon & Pina, 2010). Subsequently, it appears that firesetters' treatment needs have been presumed to be met via general offending behaviour programmes (e.g., social skills and cognitive skills programmes), evidenced by the lack of focus on developing offence-specific interventions for this population (Gannon et al, 2013;Gannon & Pina, 2010;Palmer, Caulfield, & Hollin, 2007).…”
mentioning
confidence: 99%